Study on the relationship between intrapartum group B streptococcus prophylaxis and food allergy in children - Zhang, Hong; Xu, Kang; Liu, Zhihui; Shi, Yuanmei; Li, Hui; Yin, Xiaoping (Frontiers in Pediatrics, 2022)
Objective To investigate the associations between intrapartum antibiotic prophylaxis of group B streptococcus (GBS) in pregnant women and the risk of food allergy in Chinese children Design Retrospective cohort study of 2,909 mother-child pairs. Setting Taixing People's Hospital in Eastern China. Participants Term infants born 2018–2019, followed longitudinally from birth to 3 years. Exposures The GBS-IAP was defined as therapy with intravenous penicillin G or ampicillin or cefazolin ≥4 h prior to delivery to the mother. Reference infants were defined as born without or with other intrapartum antibiotic exposure. Methods To investigate the incidence information of food allergy in children aged 18 months and three years old. Kaplan-Meier survival analysis and log-rank tests were used to evaluate the cumulative incidence in the group with GBS-IAP and the group without GBS-IAP. Cox proportional hazards models were conducted to determine the univariate and multivariate association between maternal GBS-IAP and incident food allergy after various covariates were adjusted. Results The cumulative incidence of food allergy in the group with GBS-IAP was higher than that in the group without GBS-IAP in children under 18 months old (8.1% vs. 4.5%, P = 0.005, log-rank test), but no significant differences were observed in children under three years old (9.2% vs. 7.0%, P = 0.146, log-rank test). The univariate cox proportional hazards model in children under 18 months old revealed that children in the GBS-IAP group had faster food allergy development when compared with children in the group without GBS-IAP (HR.: 1.887,95% CI: 1.207–2.950, P = 0.005), so was the multivariate model (HR.: 1.906,95% CI: 1.158–3.137, P = 0.011). However, both univariate (HR: 1.343, 95% CI: 0.891∼2.026, P = 0.159) and multivariate (HR: 1.253, 95%CI: 0.796∼1.972, P = 0.329) cox proportional hazards model in children under three years old showed no significant differences between children in the group with GBS-IAP and group without GBS-IAP. Conclusion Intrapartum antibiotic prophylaxis of group B streptococcus may increase the cumulative incidence and risk of food allergy in children under 18 months old, but it had no significant effect on children under three years old.